Stringent screening strategy significantly reduces reactivation rates of tuberculosis in patients with inflammatory bowel disease on anti‐TNF therapy in tuberculosis endemic region. Issue 11 (1st March 2022) - Kumar, Peeyush; Vuyyuru, Sudheer K.; Kante, Bhaskar; Sahu, Pabitra; Goyal, Sandeep; Madhu, Deepak; Jain, Saransh; Ranjan, Mukesh Kumar; Mundhra, Sandeep; Golla, Rithvik; Singh, Mukesh; Virmani, Shubi; et al.
Summary: Background: Anti‐tumor necrosis factor (anti‐TNF) therapy use in patients with inflammatory bowel disease (IBD) leads to an increased risk of tuberculosis (TB) reactivation despite latent tuberculosis (LTB) screening, especially in TB endemic regions. Aim: We evaluated the effect of stringent screening strategy and LTB prophylaxis on TB reactivation. Methods: We performed an ambispective comparison between patients who received anti‐TNF therapy after January 2019 (late cohort) and between Jan 2005 and Jan 2019 (early cohort). Late cohort patients were subjected to stringent screening criteria which included all: history of past TB/recent contact with active TB, chest X‐ray, CT (computed tomography) chest, IGRA (interferon‐gamma release assay), TST (tuberculin skin test), and if any positive were given chemoprophylaxis. A cohort comparison was done to evaluate for risk reduction of TB following the stringent screening strategy. Results: One hundred seventy‐one patients (63: ulcerative colitis/108: Crohn's disease, mean age diagnosis: 28.5 ± 13.4 years, 60% males, median follow‐up duration after anti‐TNF: 33 months [interquartile range: 23–57 months]) were included. Among the 112 in the early cohort, 29 (26%) underwent complete TB screening, 22 (19.6%) had LTB, 10 (9%) received chemoprophylaxis, and 19 (17%) developed TB. In comparison, in the late cohort, 100% of patients underwent complete TB screening, 26 (44%) had LTB, 23 (39%) received chemoprophylaxis, and only 1(1.7%) developed TB ( p < 0.01). On survival analysis, patients in early cohort had a higher probability of TB reactivation compared with the late cohort (HR: 14.52 (95% CI: 1.90–110.61 [ p = 0.01]) after adjusting for gender, age at anti‐TNF initiation, concomitant immunosuppression, anti‐TNF doses, and therapy escalation. Conclusion: The high risk of TB reactivation with anti‐TNF therapy in TB endemic regions can be significantly mitigated with stringent LTB screening and chemoprophylaxis. Abstract : Stringent screening strategy and chemoprophylaxis significantly reduced the reactivation rates of tuberculosis in patients with inflammatory bowel disease on anti‐TNF therapy in tuberculosis endemic region.